Synergistic Interaction of Piperine and Thymol on Attenuation of the Biofilm Formation, Hyphal Morphogenesis and Phenotypic Switching in Candida albicans - Priya, Arumugam; Nivetha, Srinivasan; Pandian, Shunmugiah Karutha (Frontiers in Cellular and Infection Microbiology, 2022)
The incidence of fungal infections has significantly increased in recent years due to the emergence of antifungal resistance. Biofilm formation is considered to be a major contributor to both the infectious diseases and to antimicrobial resistance. Consequently, biofilm-associated infections are often problematic to treat with existing therapeutics. Adhesion of C. albicans to the host surface or implanted materials followed by hyphal invasion and biofilm formation enhances C. albicans pathogenicity and virulence. Thus, developing a therapeutic agent that inhibits candidal adherence, biofilm development and morphological switching could improve clinical management of infections. The present investigation studied two emerging and alternatives strategies namely antibiofilm and combinatorial approach to attenuate biofilm formation and the expression of Candida virulence factors.. Piperine and thymol are major bioactive components of pepper and thyme, respectively. These phytochemicals are known to possess numerous biological activities, including recently reported antibiofilm effects against C. albicans. The minimum biofilm inhibitory concentration (MBIC) of both phytochemicals was determined to be 32 µg/mL. Phytochemical treatment of Candida biofilms using piperine and thymol revealed synergistic effects at four different combinations of concentrations, i.e. 8 and 8 µg/mL, 8 and 4 µg/mL, 8 and 2 µg/mL and 4 and 8 µg/mL. These synergistic combinations resulted in the significant reduction in adherence of Candida, hyphal extension, and morphological transformation. Moreover, limited exposure of synergistic combinations controlled the hyphal elongation. Results were validated through the gene expression analysis. Results from the present investigation suggest that piperine and thymol can be synergistically employed for the treatment of biofilm associated C. albicans infection.